CERMIN PERAMPASAN HAK HIDUP TAHANAN POLITIK PEREMPUAN DALAM NOVEL DARI DALAM KUBUR KARYA SOE TJEN MARCHING - Desrina Nuraffifah; Yulianeta Yulianeta; Dheka Dwi Agustiningsih (STKIP Siliwangi, 2022)
In the Orde Baru era, event 65 did not have many places in national literature. However, in this era there are quite a lot of literature works that raise the issue of event 65, one of them is a novel Dari Dalam Kubur written by Soe Tjen Marching. This novel is interesting to learn because it raised the issue of event 65 that became the historic of the Indonesian. The novel is studied using a qualitative descriptive analysis method with the sociology of literature approach by Alan Swingewood. The focus of the discussion in this research is to describe the forms of seizing of the right to life experienced by women political prisoners in event 65. The results of the study show that the novel reflects the situation in Indonesia from pre-independence, post-independence, until the Orde Baru era. The researchers found 5 reflections seizing of the right to life of women political prisoners, that is (1) arrested, (2) intimidated, (3) tortured, (4) harassed and raped, and (5) killed. There is also the suffering of Djing Fei as a ex-tapol is (1) not accepted in society, (2) stamped ET on hers identity card, (3) forced to give birth to a child as a result of raped, (4) forced to change identity, (5) lost property, and (6) moved residences. This research can help readers to understand the novel by tracing intricacies of the lives of women political prisoners described by the author through the lives of the characters in the novel.